An IVF-Twin Pregnancy Complicated with Cutaneous Polyarteritis Nodosa: A Case Report - Duru, Namık Kemal; Dede, Murat; Alanbay, İbrahim and Terek, Coşan and Gezginç, Kazım and Aksoy, Hüseyin and Ulubay, Mustafa and Başer, İskender (Gynecology Obstetrics & Reproductive Medicine, 2007)
A twin pregnancy after the Assisted Reproductive Technology (ART) complicated with cutaneous polyarteritis nodosa (PAN) is presented. A 28-years-old, nulliparous woman developed cutaneous PAN four years before the IVF-pregnancy. She had 2 years of marriage with no contraception method. After infertility work-up she was diagnosed as having unexplained infertility. Three consecutive intrauterine insemination cycles were unsuccessful. IVF with ICSI was performed and she achieved twin pregnancy. Blood pressure and biochemical analyses were normal during pregnancy. LMWH Clexane 0.4 1x1 (Enoxaparin 0.4 ml, Sanofi- Aventis) was given subcutaneously during the course of pregnancy. She underwent cesarean section because of preterm premature rupture of membranes at 33th week of gestation and delivered 2100 gr and 2240 gr male fetuses with normal Apgar scores. Management of these patients must be individualised. Systematically diagnostic evaluation of pregnancy complicated with PAN help us to determine prognosis and management.